Pengaruh Perencanaan Pajak Dan Karakteristik Keuangan Lainnya Terhadap Nilai Perusahaan - Putri Lisa; Aan Marlinah (Universitas Internasional Batam, 2021)
The purpose of this study is to analyse the effect of tax planning and other financial characteristics on firm value at non-financial sectors in Indonesia Stock Exchange. The object of this research are non-financial company in Indonesia Stock Exchange during 2017-2019. The sample of this research are 122 non-financial companies with total 366 data were used in this research based on the criteria and took a sample by purposive sampling method. The result shows that return on asset and debt to asset has significant effect to Firm Value and other independen variable such as tax planning, current ratio, firm size, dividen payout ratio, audit quality and growth do not have effect on firm value